Persistence and relapse of reinforced behavioral variability. Issue 1 (30th January 2018) - Galizio, Ann; Frye, Charles C. J.; Haynes, Jeremy M.; Friedel, Jonathan E.; Smith, Brooke M.; Odum, Amy L.
Abstract : The present study examined persistence and relapse of reinforced behavioral variability in pigeons. Pigeons emitted four‐response sequences across two keys. Sequences produced food according to a lag schedule, in which a response sequence was followed by food if it differed from a certain number of previous sequences. In Experiment 1, food was delivered for sequences that satisfied a lag schedule in both components of a multiple schedule. When reinforcement was removed for one component (i.e., extinction), levels of behavioral variability decreased for only that component. In Experiment 2, food was delivered for sequences satisfying a lag schedule in one component of a multiple schedule. In the other component, food was delivered at the same rate, but without the lag variability requirement (i.e., yoked). Following extinction, levels of behavioral variability returned to baseline for both components after response‐independent food delivery (i.e., reinstatement). In Experiment 3, one group of pigeons responded on a lag variability schedule, and the other group responded on a lag repetition schedule. For both groups, levels of behavioral variability increased when alternative reinforcement was suspended (i.e., resurgence). In each experiment, we observed some evidence for extinction‐induced response variability and for variability as an operant dimension of behavior.